Islam Jawa: Sufisme dalam Tradisi dan Etika Jawa - Kholil, Ahmad (el Harakah: Jurnal Budaya Islam, 2007)
Since long ago, Javanese ethnics were strongly related to mysticism. The people believed in the unseen which is out of human’s sense. That belief grew so fast. Hence, animism and dynamism become the first belief of Javanese at that time. When Islam first entered in the Javanese land in 14th century, the locals had believed in some sects, those are Hindu, Brahma, and Buddha. Those brought Islam into Java Island had so many works to do. It is not easy since the locals are quite fanatic with their mysticism. Islam, in progress, got positive response from the Javanese people proven by the number of Moslem at that time. Nevertheless, their ancestors’ ritual tradition still remained in the life of those Moslem. This is what makes Javanese Islam becomes the attracting topic for the cultural researchers. This article discusses all about Islam specifically in its spread history in Javanese Island starting from da’wah process to Islamic lesson which is related to Javanese philosophy. It also discusses about how the Islam conveyors tolerated with so many mystic beliefs and slowly changed those from the people. Sejak zaman dahulu, mistik dan suku Jawa sangat terkait erat. Penduduk sangat mempercayai hal gaib yang di luar nalar manusia. Kepercayaan tersebut sangat berkembang pesat. Karenanya, animisme dan dinamisme menjadi keyakinan asli penduduk suku Jawa pada masa itu. Saat Islam masuk ke tanah Jawa di abad 14, penduduk setempat telah meyakini beberapa sekte lain, yakni Hindu, Brahma, dan Budha. Tentu banyak sekali hal yang harus dilakukan bagi pembawa Islam ke tanah Jawa. Tak mudah karena penduduk masa itu sangat fanatik dengan keyakinan mistik mereka. Dalam perkembangannya, Islam mendapat respon positif dari penduduk Jawa terbukti dari banyaknya jumlah Muslim masa itu. Namun, masih banyak sekali muslim yang masih berpegang teguh pada tradisi ritual nenek moyang mereka. Hal ini menjadikan Islam Jawa menjadi pembahasan menarik bagi para peneliti budaya. Artikel ini membahas serba-serbi Islam dan penyebarannya di tanah Jawa. Mulai dari proses dakwah hingga ajaran Islam yang dikaitkan dengan falsafah Jawa. Bagaimana para penyebar Islam harus bertoleransi dengan berbagai ajaran mistis dan mengubah sedikit demi sedikit kepercayaan penduduknya.